Clinicopathological analysis of oral squamous cell carcinoma in Iraq During period (2001-2013) - Taha, Inas A; Younis, Wasan H (Journal of Baghdad College of Dentistry, 2015)
Background: Oral cancer is a highly lethal and disfiguring disease. Squamous cell carcinoma of the oral cavity constitutes about 90% of all oral malignancies. The aims of the study was to achieve an epidemiological description of the oral squamous cell carcinoma in Iraq in general and in Iraqi governorates except Kurdistan region retrospectively during period 2001-2013 Materials and Methods: Data were collected from department of oral and maxillofacial pathology, college of dentistry, university of Baghdad, Nuclear medicine and radiotherapy hospital, Iraqi cancer registry center, Main hospitals in Baghdad and Iraqi governorates, Private labs. for histopathological examinations. The descriptive and inferential statistical methods were used (frequency distributions, percentages, incidence rate, standardized ratio and relative risk) Results: In Iraq from 2001-2013, there were 1664 cases with overall M:F ratio (1.4 : 1). The most affected age group was (50-69 yrs), tongue was the most common affected site, grade II was the most common, and the highest number of OSCC was reported in Baghdad governorate. A negative time trend was observed in the overall (crude) incidence rate of all registered OSCC in Iraq. Conclusion: The incidence rate (crude rate) of OSCC decreased in Iraq from 2001 to 2013, and the standardized ratio showed that there is a decrease in tumor risk with advancing time.